Saezia sanguinis gen. nov., sp. nov., a Betaproteobacteria member of order Burkholderiales, isolated from human blood. Issue 3 (31st January 2020) - Medina-Pascual, María J.; Monzón, Sara; Villalón, Pilar; Cuesta, Isabel; González-Romo, Fernando; Valdezate, Sylvia
Abstract : The taxonomic position of an unknown bacterial strain designated CNM695-12, isolated from the blood of an immunocompromised subject, was investigated via phenotypic, chemotaxonomic, genotypic and genomic analyses. Bacterial cells were determined to be Gram-stain-negative bacilli, aerobic, non-motile and non-spore-forming. The strain showed catalase activity but no oxidase activity. Optimal growth occurred at 37 °C, pH 7 and with 0–1 % NaCl. C16 : 0, summed feature 8 (comprising C18 : 1 ω7 c / ﻿C18:1 ω6 c ), and C18 : 1 ω9 c were the most abundant fatty acids, and ubiquinone 8 was the major respiratory quinone. The polar lipids present included phosphatidylglycerol, phosphatidylethanolamine and other aminophospholipids. The 16S rRNA gene sequence showed approximately 93.5 % similarity to those of different species with validly published names within the order Burkholderiales (e.g. Leptothrix mobilis Feox-1 T, Aquabacterium commune B8 T, Aquabacterium citratiphilum B4 T and Schlegelella thermodepolymerans K14 T ). Phylogenetic analyses based on 16S rRNA gene sequences and concatenated alignments including the sequences for 107 essential proteins, revealed the strain to form a novel lineage close to members of the family Comamonadaceae . The highest average nucleotide identity and average amino acid identity values were obtained with Schlegelella thermodepolymerans K14 T (69.6 and 55.7 % respectively). The genome, with a size of 3.35 Mb, had a DNA G+C content of 52.4 mol% and encoded 3056 predicted genes, 3 rRNA, 1 transfer–messengerRNA and 51 tRNA. Strain CNM695-12 thus represents a novel species belonging to a novel genus within the order Burkholderiales, for which the name Saezia sanguinis gen. nov., sp. nov. is proposed. The type strain is CNM695-12 T (=DSM 104959 T =CECT 9208 T ).